Analisis Perilaku Konsumen terhadap Keputusan Pembelian dan Loyalitas Pelanggan Suplemen di Apotek - Sofia Anisa Umar; I Gede Made Wirabrata; Rafrini Amyulianthy (TIN: Terapan Informatika Nusantara, 2026)
The increasing public awareness of maintaining body immunity after the COVID-19 pandemic has driven the growth of dietary supplement consumption as a preventive health measure. However, fluctuating supplement sales indicate the presence of factors influencing consumer behavior in purchasing decisions and customer loyalty. This study aims to analyze the effects of knowledge, attitude, and behavior on purchasing decisions and customer loyalty toward supplements. The research employed a quantitative method with a descriptive approach, involving 150 respondents who had purchased supplements, using a questionnaire with a 1–5 interval scale. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS software. The results show that knowledge (0.411; 0.297), attitude (0.290; 0.220), and behavior (0.275; 0.233) have positive and significant effects on purchasing decisions and customer loyalty. Purchasing decisions also have a significant positive effect on customer loyalty with a path coefficient of 0.314. Additionally, knowledge (0.129), attitude (0.091), and behavior (0.087) indirectly influence customer loyalty through purchasing decisions. These findings indicate that better consumer understanding and positive attitudes contribute to repeat purchases and stronger customer loyalty. Therefore, improving product education, ensuring product availability, and enhancing service quality with a customer-oriented approach are essential strategies to strengthen customer loyalty.